The role of education in the countries of origin in addressing the trafficking of young Nigerian women to Europe (Educational Knowledge, 2018)
This article is the result of the research project “Human Trafficking, Comprehensive Health, and Care: Cross-Border Women in Transit from Morocco to Andalusia,” conducted by Pablo de Olavide University in 2014. In Europe, and specifically in Spain, the trafficking of increasingly younger women, including minors, of Nigerian origin for the purpose of sexual exploitation is a growing reality. The research, using a qualitative approach and based on observations, interviews, and creative storytelling workshops, analyzes the conditions in the countries of origin that contribute to trafficking, paying particular attention to the role of formal education. It also presents an experience of peer education. The results show that Nigerian trafficking involves multiple vulnerabilities in the countries of origin, where lack of education is a key factor. Furthermore, the research highlights the potential of peer awareness-raising as a means of fostering transformative reflection.
Keywords: trafficking in human beings; education; gender; creative narratives.